Evaluation of Knowledge, Attitude, and Approaches Regarding the COVID-19 Pandemic among the General Population in a Suburban City of Western India: A Cross-sectional Study - Badgujar, Jatin; Kadam, Rahul; Sharma, Gaurav; Shah, Akshay; Relwani, Nisha (Disease and Health Research: New Insights Vol. 11, 2024)
Background: The ongoing coronavirus (COVID-19) pandemic was first reported following an outbreak of respiratory tract illness in Wuhan, the capital city of Hubei province, in Central China on 29th December 2019 [1-3]. As of 14 June 2020, there have been 7,860,524 confirmed cases of COVID-19 including 431,918 deaths in 213 countries and territories around the world. The aim of the present study was to assess the knowledge, attitude, and practices (KAP) regarding the COVID-19 pandemic among the general population. Methods: A cross-sectional study was conducted among the general population residing in Navi Mumbai, India, by distributing an online-based predesigned, prevalidated, and semi-structured survey questionnaire through social media from 20 April to 27 April 2020. The survey instrument consisted of questions based on demographic characteristics, followed by knowledge (12 questions), attitude (11 questions), and practices (5 questions). Individuals above 18 years of age, able to understand the English language, and willing to voluntarily consent were included in the study. The final results were expressed as mean with standard deviation and p<0.05 was considered to be statistically significant. The final analysis was done using Epi Info software (version 3.4.3) and Microsoft Excel 2013 (Microsoft Office version 15.0). Results: A total of 817 participants were included in the study. The mean knowledge score was 10.04±1.52 with an overall accurate response rate of 83.70%. Most of the participants had a positive attitude regarding the COVID-19 pandemic. A positive correlation was found between level of education with mean knowledge scores as well as positive attitude towards COVID-19 using the Kruskal-Wallis H test (non-parametric ANOVA), which was statistically significant (p<0.001). The majority of participants followed infection prevention guidelines, including the use of a facemask (94.61%), appropriate hand hygiene practices (93.26%), maintaining social distancing (97.42%), and avoiding direct personal contact through handshake/hugging (97.42%). Conclusions: The study highlights the importance of a level of education with correct knowledge, a positive attitude, and appropriate practices. The information can further assist policymakers in predicting success or making necessary modifications with respect to infection mitigation measures based on the knowledge, attitude, and practices of the targeted population. A higher level of education helps to improve compliance of infection preventive measures formulated by policymakers among the general population which translates into improved overall outcomes and to focus on targeted interventions.